-2(2x-6)=32

Simple and best practice solution for -2(2x-6)=32 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(2x-6)=32 equation:


Simplifying
-2(2x + -6) = 32

Reorder the terms:
-2(-6 + 2x) = 32
(-6 * -2 + 2x * -2) = 32
(12 + -4x) = 32

Solving
12 + -4x = 32

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + -4x = 32 + -12

Combine like terms: 12 + -12 = 0
0 + -4x = 32 + -12
-4x = 32 + -12

Combine like terms: 32 + -12 = 20
-4x = 20

Divide each side by '-4'.
x = -5

Simplifying
x = -5

See similar equations:

| 6x^2=x-24 | | 7x-10+x+4=90 | | -4=(-2) | | -4=(0) | | 7x-10+x+4=180 | | 24x-3y-18=0 | | -2=(2) | | 2pq+pq= | | 6*(x+2)= | | (-14)+3= | | 2+3y=19 | | -4=2 | | 4+x=-10 | | 4x+21+11x+9=180 | | 9g-13=2g | | 7-15=-(3-8) | | 3n+7=4 | | 7x-10=x+4 | | y+2=-3(-2)+8 | | c+6=-3 | | y+2=-3(0)+8 | | -3.1+x=-2.1 | | 6a-3=2 | | y+2=-3(2)+8 | | -3x(2x-3)=-5x+5 | | 6n+3=-2n+12 | | 6+3=3-3y | | -6(-2)+5=y | | 13+a=11 | | 125n^3-50n^2+100n-40= | | 1/2x-3y=-9 | | -6(0)+5=y |

Equations solver categories